Microsurgical reconstruction of major scalp defects following scalp avulsion - Gurdayal Singh Kalra; Pradeep Goil; Pranay S Chakotiya (Indian Journal of Plastic Surgery)
Introduction: Total scalp avulsion is a serious injury, commonly occurring in Indian females working with industrial and agricultural machines. Their long hairs often get caught in a rapidly revolving machines, resulting in total avulsion of scalp. Lack of education and awareness in Indian villages often result in these patients coming late to the hospitals when replantation is not possible and scalp reconstruction remains the only available option. Materials and Methods: We performed our study on 22 cases of scalp avulsion injury presented to us between June 2007 and April 2012 at Department of Burn, Plastic & Reconstructive Surgery, SMS Hospital, Jaipur. In all of them a free tissue transfer was performed as an elective procedure. Results: Twenty two patients underwent free tissue transfer and followed up for an average period of 6 months. All patients included in this study were females with mean age of 28 yrs. Five patients in our study reported with partial necrosis of the free flaps which were subsequently managed with split-thickness skin graft (STSG). Two patients reported total necrosis of the flap which was re-operated using latissimus dorsi along with serratus anterior muscle (LDSA) from the contralateral side. Conclusion: As scalp avulsion because of rapidly rotating machine leads to large size defect not amenable for local tissue reconstruction. We performed reconstruction using LDSA and omental free flaps with split thickness skin graft (STSG) for large scalp defect and achieved good and stable soft tissue cover with satisfactory cosmesis.